Powerful bidders and value creation in M&As - Tunyi Tunyi Abongeh (International Review of Financial Analysis, 2022)
This paper explores the role of bargaining ability in corporate mergers and acquisitions (M&As) by focusing on acquiring firms with ex-ante market power—powerful bidders. Drawing from a bargaining power theoretical stance, we argue that powerful bidders create value from M&A activity by paying comparatively lower premiums. We test our empirical proposition using a sample of 9327 M&A deals announced between 2004 and 2016 by bidders across 30 countries. Contrary to the stylized fact that bidders do not gain from M&A activity, we uncover evidence suggesting that powerful bidders pay lower bid premiums and, consequently, earn positive (and relatively higher) cumulative announcement returns (CARs) from M&A deals. On average, the mean returns to powerful bidders (1.3%) are at least twice those of their less powerful counterparts (0.6%). We identify “low financial constraints” as a potential channel through which higher bidder power translates to improved deal performance. Overall, our results provide new evidence on how industry dynamics, notably bargaining power, influences M&A outcomes.